Interpreting The Impetus of Artificial Intelligence (AI) On Customer Satisfaction in The Digital Banking Landscape - Joseph A, Sunil; C M, Shiny (Universitas Prasetiya Mulya, 2024)
Artificial Intelligence (AI) transforms digital banking technology by augmenting the consumer banking experiences. This study explored the stimulus of AI attributes-trendiness, visual attractiveness, and problem-solving on customer satisfaction in digital banking. To accomplish this, a descriptive and quantitative research approach was embraced, gathering and analysing 120 sample using SPSS 23.0. The correlation analysis exposed positive association between AI attributes and customer satisfaction. Trendiness indicated a modest correlation, Visual Attractiveness and Problem Solving exhibited robust correlations. The regression analysis proved that visual attractiveness is exceptionally significant, problem solving exhibited significant impact and trendiness did not forecast substantial customer pleasure. This study emphasizes the significance of visual attractiveness and problem-solving in shaping positive customer experiences in AI-induced digital banking, stressing the necessity for the constant innovation in the competitive business environment.